Measuring the Agricultural Sustainability in Rural Areas- A Case Study: Rural Areas of Central District of Ravansar Township - Eskandar Seydaei; Yousuf Ghanbari; Davoud Jamini; Mohammadreza Boshagh (جغرافیا و پایداری محیط)
Sustainable and continuous development of each country is dependent upon Sustainability of it’s agricultural system. In countries which are dependent on rural economy, sustainable agricultural development is of great importance economically, socially, culturally, and politically. The main objective of this study is to investigate the agricultural sustainability in rural areas with the focus on the central district of Ravansar township. The research takes the design of descriptive analysis in which data are collected through instruments used in field studies. Population of the study included the heads of rural families in all villages of Central district in Ravansar (N=4209). Using Cochran formula and stratified sampling, a sample of 188 people was selected and surveyed through questionnaires. In order to estimate the reliability of the research, Cronbachs' alpha coefficient was used and indicated the coefficient of 0.72, 0.73, 0.79 percent for three parts of the questionnaire, representing the appropriateness of the instruments used. The results of statistical analysis in SPSS software show that 55 percent of indicators have been in the unsustainable group, 36.5 percent in somewhat sustainable group.